Synthesis of 5-substituted 1H-tetrazoles Using Natural and Reusable Natrolite Zeolite - Mohammad Sajadi, S.; Mahamb, Mehdi (Letters in Organic Chemistry, 2014)
During this study the application of Natrolite zeolite was investigated as a solid acid catalyst for efficient preparation of 5-substituted 1H-tetrazole derivatives. Excellent yields of products were obtained with a wide range of substrates. After completion of the reaction, the catalyst was recovered by filtration and reused several times with only a slight decrease of activity observed under the same reaction conditions.
Keywords: heterogeneous catalyst